Working-Class Legislators and Perceptions of Representation in Latin America. (December 2019) - Barnes, Tiffany D.; Saxton, Gregory W.
How does the near-exclusion of working-class citizens from legislatures affect citizens' perceptions of representation? We argue that when groups of people are continually denied access to representation, citizens are less likely to believe that their interests are represented by the legislature. By contrast, more inclusive institutions that incorporate members of the working class foster support for representative bodies. Using a multilevel analysis of eighteen Latin American countries—a region plagued by disapproval of and disenchantment with representation—we find that greater inclusion of the working class is associated with better evaluations of legislative performance. These findings have important implications for strengthening democracy in Latin America, as they indicate that more diverse political institutions may be key to deepening citizens' attachments to representative bodies.